The ethics of humanitarian aid in conflict situations - Allen, Timothy (Department of Philosophy, 2015)
The plight of people suffering from the violence and deprivation of conflict attracts a great deal of aid. Such aid is often inspired by the thought that we have some responsibility to protect or assist innocent victims of war. However, this humanitarian response is vulnerable to abuse. Combatants can manipulate the supply of aid to achieve their ends, or channel aid to provide their forces with additional food or arms, and so extend the conflict. This poses a challenge to our obligation to assist victims of conflict: if the aid hurts more than it helps, a reasonable response is to refrain from giving aid. This may not help people in need, but it avoids hurting them further. A better response would be to find another means of helping people trapped by conflict which does not risk making their positions worse. This dissertation explores a variety of means that might enable us to help victims of conflict, such as redirecting aid, intervening militarily, or enacting sanctions. One promising strategy involves removing or altering certain international rules which have a role in encouraging conflict. Altering these rules requires concerted advocacy and political will, but given sufficient attention, such an approach could shorten or reduce the severity of some conflicts, or curtail their ill effects on civilians.